An Experimental Study of Weibull and Rayleigh Distribution Functions of Wind Speeds in Kosovo - Bukurie Hoxha; Rexhep Selimaj; Sabrije Osmanaj (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper compares two commonly used functions, the Weibull and Rayleigh distribution functions, for fitting a measured wind speed probability distribution at a given location over a certain period. The monthly and annual measured wind speed data at 84 m height for the years have been statistically analyzed for the country with a large capacity - Kitka. The analysis is made in the case of the implementation of all the predicted capacity of wind turbines and by virtue of the probability of power distribution. The Weibull and Rayleigh probability distribution functions have been determined and their parameters have been identified. The average wind speed and the wind power density have been estimated using both distribution functions and compared those estimated from the measured probability distribution function. The Weibull distribution function fits the wind speed variation better than Rayleigh distribution function. The average wind speed was found to be 4.5 m/s and the average wind power density was 114.54 W/m According to results, we can conclude that such a distribution of winds in this region yields an appropriate average value of wind power.